2019
DOI: 10.19041/apstract/2019/1-2/3
|View full text |Cite
|
Sign up to set email alerts
|

Goat Keeping and Goat Milk Products in Human Nutrition - Review

Abstract: The aim of this paper is to review the status quo and future perspective of goat keeping and goat milk products, particularly emphasising the role of goat milk products in human nutrition. Across the globe, goats can be kept almost anywhere, even in poor surroundings. Considering the deteriorating geographical conditions due e.g. to global warming, the importance of goat and goat products will probably further increase. Goats can play an important role in the nutrition of the continuously increasing human popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…Among its characteristics, it is observed that it has a higher proportion of essential amino acids (52.5%) compared to dairy milk (46.7%) and sheep milk (48%), and compared with buffalo milk, goat milk has a higher concentration of most of the essential amino acids, except valine and isoleucine [18]. It has five times more folic acid than human milk and six times more than dairy milk [19]. It contains fat globules that are smaller than 3.5 µg, which facilitates its digestion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among its characteristics, it is observed that it has a higher proportion of essential amino acids (52.5%) compared to dairy milk (46.7%) and sheep milk (48%), and compared with buffalo milk, goat milk has a higher concentration of most of the essential amino acids, except valine and isoleucine [18]. It has five times more folic acid than human milk and six times more than dairy milk [19]. It contains fat globules that are smaller than 3.5 µg, which facilitates its digestion.…”
Section: Introductionmentioning
confidence: 99%
“…It also exhibits antimicrobial activity due to containing lactoferrin, lactoperoxidase, lysozymes, and peptide precursors to components of immunity [20,21]. Finally, it reduces the risk of anemia and bone demineralization because of its high levels of iron, calcium, and phosphorus [19].…”
Section: Introductionmentioning
confidence: 99%
“…Goat milk proteins have different ratios of caseins and whey proteins than cow's milk, resulting in different functional properties (Qin et al, 2021 ). Thus, goat milk proteins show promise for use in a variety of food products, especially for those who are sensitive to cow milk (Csapóné Riskó & Csapó, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Молоко козы содержит в 6 раз больше кобальта, который входит в состав витамина В12 (0,1 мкг). Как известно данный витамин отвечает за кроветворение и контролирует обменные процессы [5,6].…”
Section: Introductionunclassified